Ekstrak Air Umbi Ubijalar Ungu Menurunkan Total Kolesterol serta Meningkatkan Total Antioksidan Darah Kelinci - Jawi, I Made; Budiasa, Ketut (Jurnal Veteriner, 2012)
High cholesterol diet can increase blood total cholesterol and the incidence of cardiovascular disease.Flavonoid from fruits and vegetables can prevent those conditions due to it’s antioxidant effect. The aimof this study was to examine hypolipidemic and antioxidant possible effects of water extract of purplesweet potato, on blood of local rabbit with high cholesterol diet. This studies used 20 female adult localrabbit which were divided into 2 groups by using randomized pre-test and post-test control group design.Before treatment blood samples were collected from auricula venous to examine the total cholesterol, LowDensity Lipoprotein(LDL), High Density Lipoprotein (HDL), triglyseride, malondialdehide (MDA), totalantioxidant, Serum Glutamic Oxaloacetic Transaminase (SGOT), Serum Glutamic Piruvic Transaminase(SGPT), and haemoglobin concentration, as pretest data. After pre-tests, group 1 was given high cholesteroldiet without water extract of purple sweet potato. In contrast group 2 was given high cholesterol diet withwater extract of purple sweet potato. After 3 months of the treatment the blood were collected for posttestexamination. The data was analysed by using t-test. The result showed a significant increase in totalcholesterol, LDL, SGOT,SGPT, and MDA in the blood of group 1( p<0,05), whereas there was a significantdecrease in HDL at the same group (p<0,05). However, after 3 months of the treatment, all of the parametersin group 2 (except the total cholesterol) were not significantly different with the pretest result (p>0.05),although there was a significant difference compared to the control group (p<0.05). Total cholesterol wassignificantly decreased after 3 months of treatment in group 2 (p<0,05). It can be concluded that waterextract of purple sweet potato can keep the lipid profiles in normal range values, prevent the increase ofMDA, increase blood total antioxidant, decrease blood total cholesterol, and safe for the rabbit liver thatgiven high cholesterol diet.
Keywords: lipid profile, purple sweet potato, rabbit, total antioxidant